VISTA Expression on Immune Cells Correlates With Favorable Prognosis in Patients With Triple-Negative Breast Cancer - Cao, Xi; Ren, Xinyu; Zhou, Yidong; Mao, Feng; Lin, Yan; Wu, Huanwen; Sun, Qiang (Frontiers in Oncology, 2021)
V-domain Ig suppressor of T-cell activation (VISTA), a newly discovered negative immune checkpoint, is thought to be related to immunotherapy resistance and may become a new immune therapeutic target. Here, we evaluated the expression of VISTA in a cohort containing 254 patients with untreated triple-negative breast cancer. The relevance of VISTA expression, clinicopathologic parameters, expression of other immune markers and prognosis were investigated in the whole cohort. Genomic analysis of 139 triple-negative breast cancer(TNBC) patients from the cancer genome atlas (TCGA) was also performed. VISTA was expressed in the immune cells (ICs) and in the tumor cells (TCs) in 87.8% (223/254) and 18.5% (47/254) of the cohort, respectively. VISTA-positive ICs were associated with no lymph node metastasis (p<0.001), American Joint Committee on Cancer (AJCC) stage I and II (p=0.001) and basal-like subtype (p<0.001). VISTA expression in ICs positively correlated with some tumor-infiltrating lymphocytes (TILs) types, particularly with the CD4+TILs , which was consistent with mRNA level analysis from the TCGA datebase. Survival analysis showed that patients with VISTA-positive ICs had prolonged relapse-free and overall survival compared with the negative ones, especially among T1-2N0 stage patients. Multivariate analysis showed that it independently predicted the prognosis. These data confirmed the regulatory role of VISTA in anti-tumor immunity, changed our perception of VISTA as a negative immune checkpoint,and suggested VISTA as a potential therapeutic target for TNBC.